Kesehatan Mental Mahasiswa Fakultas Kedokteran Di Masa Pandemi COVID-19 - Athaya Taufiqy (Puslitbang Sinergis Asa Professional, 2021)
December 2019, COVID-19 was first reported in Wuhan, Hubei Province, China. March 11, 2020, the World Health Organization declared COVID-19 a worldwide pandemic. The COVID-19 pandemic has focused attention on the mental health of the various affected populations, medical students being one of the more vulnerable groups. Therefore, this literature review aims to find out how the mental health of Faculty of Medicine students during the COVID-19 pandemic, so that it can be used as learning material to always maintain mental health stability. The method used in this study is a literature review and literature search which was carried out by collecting several electronic journals such as PubMed, NCBI and Google Scholar. Conducted by reviewing journals related to the mental health of medical faculty students during the COVID-19 pandemic. This study involved 49 library sources from 2018-2020. From 7,143 students, 0.9% of them experienced severe anxiety, 2.7% moderate, and 21.3% experienced mild anxiety. In addition, delay in academic activities is a risk factor for experiencing symptoms of anxiety. 40% of students also experience financial difficulties, in terms of e-learning platforms, this problem is a challenge for medical students because financial and social factors can be an obstacle to the development and implementation of effective online learning programs. Future research is urgently needed to provide a better explanation of the tips needed for students in adapting to the changes that occur in order to lead a mentally healthy life in the midst of the COVID-19 pandemic.